2019
DOI: 10.1186/s12866-019-1433-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide discovery of structured noncoding RNAs in bacteria

Abstract: BackgroundStructured noncoding RNAs (ncRNAs) play essential roles in many biological processes such as gene regulation, signaling, RNA processing, and protein synthesis. Among the most common groups of ncRNAs in bacteria are riboswitches. These cis-regulatory, metabolite-binding RNAs are present in many species where they regulate various metabolic and signaling pathways. Collectively, there are likely to be hundreds of novel riboswitch classes that remain hidden in the bacterial genomes that have already been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 73 publications
4
84
0
1
Order By: Relevance
“…A recently developed computational pipeline has been used to identify novel classes of ncRNA candidates in several bacterial genomes [34]. Among the 30 ncRNA candidates discovered, a putative RS was found associated with genes involved in the biosynthesis of TPP, in particular with thiS (encoding for a sulphur carrier protein involved in the synthesis of thiamine), and therefore termed thiS motif.…”
Section: Discussionmentioning
confidence: 99%
“…A recently developed computational pipeline has been used to identify novel classes of ncRNA candidates in several bacterial genomes [34]. Among the 30 ncRNA candidates discovered, a putative RS was found associated with genes involved in the biosynthesis of TPP, in particular with thiS (encoding for a sulphur carrier protein involved in the synthesis of thiamine), and therefore termed thiS motif.…”
Section: Discussionmentioning
confidence: 99%
“…4). One exception was a riboswitch candidate originally called thiS (Stav et al 2019). Representatives of this class are always associated with genes coding for enzymes that synthesize the TPP biosynthetic intermediate hydroxyethyl-thiazole phosphate (HET-P) (Begley et al 1999).…”
Section: This Motif Rnas: Riboswitches For Hmp-ppmentioning
confidence: 99%
“…Despite these clues, ligand binding assays initially failed to reveal the natural ligand for this riboswitch class. However, the use of riboswitch reporter-fusion constructs and bacterial strains with knockouts of genes in the TPP biosynthetic pathway revealed that another intermediate, HMP-PP, was the ligand (Stav et al 2019;Atilho et al 2019). The riboswitch senses the build-up of HMP-PP to activate the expression of genes involved in producing HET-P, which together form the final coenzyme product.…”
Section: This Motif Rnas: Riboswitches For Hmp-ppmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, RNA switches belonging to just one type of bacteria or without a conserved sequence or known regulatory mechanism may be missed using this methodology. Thus, there is the potential that additional novel RNA switches exist, especially considering the vast number of molecules within a cell (Stav et al, 2019). Since known RNA switches have been found predominately within the 5′UTR of transcripts, we chose to first perform a search for new candidates within the 5′UTRs.…”
Section: Discovery Of a Transcription Attenuation Mechanism Via Strucmentioning
confidence: 99%